Prognostic impact of diagnostic and treatment delays in children with osteosarcoma. Issue 4 (11th January 2020) - Vasquez, Liliana; Silva, Jose; Chavez, Sharon; Zapata, Arturo; Diaz, Rosdali; Tarrillo, Fanny; Maza, Ivan; Sialer, Luis; García, Juan
Abstract: Background: The aim of this study is to evaluate the relationship between the latency to diagnosis (LD) and the time to completion of chemotherapy (TCC) with clinical outcomes in children with osteosarcoma. Methods: We performed a retrospective analysis of all patients who received treatment for osteosarcoma in two tertiary centers in Peru from 2008 to 2015. All causes of delayed LD or TCC were evaluated. Overall survival (OS) and event‐free‐survival (EFS) were estimated and compared according to LD, TCC, and established clinical prognostic factors. Results: One hundred and thirteen patients were included in the study. The median LD was 13.5 weeks (interquartile range, 10‐18.5 weeks). No association was observed among clinical stage, tumor size, and LD. Delayed LD was not associated with a worse clinical outcome. Multivariate analysis confirmed that OS and EFS were significantly worse in cases of a delayed TCC (≥4 weeks), with hazard ratios of 2.70 (1.11‐6.76, P  = 0.003) and 1.13 (1.00‐1.26, P  = 0.016), respectively. Most delays in TCC (85%) were due to extramedical reasons (e.g., lack of available hospital beds). Conclusion: The LD did not seem to influence the EFS and OS in pediatric patients with osteosarcoma. However, a delay in TCC from any cause is independently associated with poor outcome in pediatric patients with osteosarcoma. Based on these results, further efforts may be needed to avoid treatment delays in patients with osteosarcoma in middle‐income countries.